Innovative haricot beans (Phaseolus vulgaris) seed system for smallholder farmers in Dale District, Southern Ethiopia: Experiences from IPMS - Yilma, Y.; Berhe, Kahsay; Hoekstra, Dirk; Jaleta, Moti; Alemayehu, F.; Gebrehawariat, K.; Ayele, D. (International Livestock Research Institute, 2010)
The demand for haricot bean (Phaseolus vulgaris), both in domestic and export markets, has been increasing in the past decade. This development can be exploited by smallholders to increase their income through increased market participation. To assist in this development, the Improving Productivity and Market Success (IPMS) of Ethiopian Farmers Project introduced a participatory market oriented value chain development approach with the key actors: farmers groups, the Woreda OoARD, farmers’ cooperative, Melkassa and Hawassa Agricultural Research Centres (ARC), and the International Centre for Tropical Agriculture (CIAT). Farmers traditionally used red colored varieties (Red Wolayita), mainly for home consumption. Shortage of high quality seed in the required quantities has inhibited many farmers from growing haricot beans. The problem is furthermore aggravated by the fact that farmers in the southern region do not keep or preserve seed stock until the next season due to the vulnerability of haricot bean seed to storage pests. The project partners introduced/tested various interventions including variety testing, seed multiplication and market linkages using different approaches and tools. Among the five varieties tested, Nasir, Dimtu and Ibado (logomame) were identified as suitable for a more commercial oriented haricot bean production system. However, DRK and Cranscope were found to be less suitable. In 2008, 51 farmers in 7 PAs, organized in clusters, started producing seeds of improved varieties and produced about 83 qt of seeds. In 2009 the number of farmers and PAs had grown respectively to 103 and 11. However, due to poor rainfall no seeds were harvested in the same year. In 2008, the Weynenata cooperative was selected to purchase seeds from seed producers with credit provided from the IPMS innovative credit fund. About 4.3 tones of semi-certified seed were processed/stored and packed in 6,010 labeled packets. Farmers appreciated the labeling, but preferred larger sized packs. An obvious challenge is the variability of rainfall, which affected the viability of the commercialization of haricot bean grain and seed production. Attention also needs to be paid to strengthening linkages between partners; and cooperatives in its marketing role. Linkages between the cooperative and private sales outlets should be considered for the sale of packed seeds.